The scientific value and potential of New Zealand swamp kauri. (1st March 2018) - Lorrey, Andrew M.; Boswijk, Gretel; Hogg, Alan; Palmer, Jonathan G.; Turney, Christian S.M.; Fowler, Anthony M.; Ogden, John; Woolley, John-Mark
Abstract: New Zealand swamp kauri ( Agathis australis ) are relic trees that have been buried and preserved in anoxic bog environments of northern New Zealand for centuries through to hundreds of millennia. Kauri are massive in proportion to other native New Zealand trees and they can attain ages greater than 1000 years. The export market for swamp (subfossil) kauri has recently been driven by demand for a high-value workable timber, but there are concerns about the sustainability of the remaining resource, a situation exacerbated in recent years by the rapid extraction of wood. Economic exploitation of swamp kauri presents several unique opportunities for Quaternary science, however the scientific value of this wood is not well understood by the wider research community and public. Here, we summarise the history of scientific research on swamp kauri, and explore the considerable potential of this unique resource. Swamp kauri tree-ring chronologies are temporally unique, and secondary analyses (such as radiocarbon and isotopic analyses) have value for improving our understanding of Earth's recent geologic history and pre-instrumental climate history. Swamp kauri deposits that span the last interglacial-glacial cycle show potential to yield "ultra-long" multi-millennia tree-ring chronologies, and composite records spanning large parts of MIS3 (and most of the Holocene) may be possible. High-precision radiocarbon dating of swamp kauri chronologies can improve the resolution of the global radiocarbon calibration curve, while testing age modelling and chronologic alignment of other independent long-term high-resolution proxy records. Swamp kauri also has the potential to facilitate absolute dating and verification of cosmogenic events found in long Northern Hemisphere tree-ring chronologies. Future efforts to conserve these identified values requires scientists to work closely with swamp kauri industry operators, resource consent authorities, and export regulators to mitigate potential losses to science as this precious material is progressively extracted from the ground and utilized. Highlights: Swamp kauri chronologies cover parts of the last interglacial-glacial cycle that are not known for other tree ring records. "Ultra-long" multi-millennia tree ring chronologies spanning large parts of MIS3 are possible. Radiocarbon calibration and climate reconstructions using ring widths and ring chemistry remain high priorities. Potential to investigate ENSO activity using swamp kauri that grew under different global climate boundary conditions. High-precision dating of swamp kauri can improve the global radiocarbon calibration curve and ability to align proxy archives.